Saving our national icon: An ecological analysis of the 2011 Australian Senate inquiry into status of the koala. Issue 54 (December 2015) - Shumway, Nicole; Lunney, Daniel; Seabrook, Leonie; McAlpine, Clive
Highlights: Public submissions to the Australian Senate inquiry into the status of the koala were reviewed. Three concerns stood out: habitat clearing, ineffective policies, and infrastructure development. Results were compared to Senate Inquiry report and its recommendations. Results suggest the Senate report recommendations were inaccurate and spatially bias. Key implications for species conservation policy discussed in conclusions.